Pesticide exposure and risk of monoclonal gammopathy of undetermined significance in the Agricultural Health Study - Landgren, Ola; Kyle, Robert A; Hoppin, Jane A; Beane Freeman, Laura E; Cerhan, James R; Katzmann, Jerry A; Rajkumar, S Vincent; Alavanja, Michael C (Blood, 2009)
Pesticides are associated with excess risk of multiple myeloma, albeit inconclusively. We included 678 men (30-94 years) from a well-characterized prospective cohort of restricted-use pesticide applicators to assess the risk of monoclonal gammopathy of undetermined significance (MGUS). Serum samples from all subjects were analyzed by electrophoresis performed on agarose gel; samples with a discrete or localized band were subjected to immunofixation. Age-adjusted prevalence estimates of MGUS were compared with MGUS prevalence in 9469 men from Minnesota. Associations between pesticide exposures and MGUS prevalence were assessed by logistic regression models adjusted for age and education level. Among study participants older than 50 years (n = 555), 38 were found to have MGUS, yielding a prevalence of 6.8% (95% CI, 5.0%-9.3%). Compared with men from Minnesota, the age-adjusted prevalence of MGUS was 1.9-fold (95% CI, 1.3- to 2.7-fold) higher among male pesticide applicators. Among applicators, a 5.6-fold (95% CI, 1.9- to 16.6-fold), 3.9-fold (95% CI, 1.5- to 10.0-fold), and 2.4-fold (95% CI, 1.1- to 5.3-fold) increased risk of MGUS prevalence was observed among users of the chlorinated insecticide dieldrin, the fumigant mixture carbon-tetrachloride/carbon disulfide, and the fungicide chlorothalonil, respectively. In summary, the prevalence of MGUS among pesticide applicators was twice that in a population-based sample of men from Minnesota, adding support to the hypothesis that specific pesticides are causatively linked to myelomagenesis.